2011
DOI: 10.1210/en.2011-0288
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Interferon-γ Results in Reduced Body Weight and Better Glucose Tolerance in Mice

Abstract: Obesity is a chronic low-grade inflammatory disease caused by increased energy intake and reduced energy expenditure. Studies using animal models with deletion of inflammatory cytokines have produced conflicting results with some showing increased weight gain and others showing no effect or even reduced body weights. Clearly, more work is necessary to understand the role of cytokines on body weight control. The aim of this study was to determine the effect of interferon-γ deletion (IFNγ(-/-)) on body weight re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 45 publications
(59 reference statements)
2
62
0
1
Order By: Relevance
“…The increased INFG mRNA is a clear sign for inductions of gingival inflammation, since interferon γ is an activator for both innate and adaptive immunity. Wong et al (2011) demonstrated that restricting interferon γ in mice improved their glucose metabolism. There was also a significant increase in CEBPA, which encodes for CCAAT/enhancer-binding protein α that controls transcriptions of GCSF and IL6R genes and therefore affects granulocytes differentiation (Zhang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The increased INFG mRNA is a clear sign for inductions of gingival inflammation, since interferon γ is an activator for both innate and adaptive immunity. Wong et al (2011) demonstrated that restricting interferon γ in mice improved their glucose metabolism. There was also a significant increase in CEBPA, which encodes for CCAAT/enhancer-binding protein α that controls transcriptions of GCSF and IL6R genes and therefore affects granulocytes differentiation (Zhang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…(12) The cytokine IFN-γ, which is predominantly derived from T cells and natural killer T cells, (13) plays an important role in the innate and adaptive immune responses, particularly regarding viral infections. Because IFN-γ is primarily secreted by T cells and natural killer T cells, (14) emerging evidence suggests that increases in the T-cell population in adipose tissue and leptin modulation of T cells to a Th1 immune response, with increased production of IFN-γ, (12,14) contribute to obesity in subjects with a specific asthma phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Precisely because the IFN-γ is high in obesity, studies suggest that this cytokine impairs glucose homeostasis and body weight control [8][9][10] .…”
Section: Ifn-γ Is a Cytokine Produced By T And Natural Killer Cells (Nk)mentioning
confidence: 99%
“…It has been shown that during obesity, elevated concentrations of IFN-γ favor the body weight gain and impair the glucose homeostasis [8][9][10] . However, the suppression of this mediator promotes inverse effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation